"Ob Dir es sauer wird mit Deiner Nahrung und Ackerwerk, das laß Dich nicht verdrießen, denn Gott hat es also geschaffen" - Gottfreid Dietrich Wilhelm Berthold (1854 - 1937) Ein Beitrag zur Geschichte der Biologie an der Georgia Augusta Göttingen - Ruttig, Katharina (Universitätsverlag Göttingen, 2012)
Gottfried Dietrich Wilhelm Berthold (1854-1937) was one the foremost botanists and phycologists at the end of the 19th century. Born and educated in Westphalia, he enrolled at the Georgia Augusta to study plant sciences and focused on algae. After research stays at the Zoological Station at Naples he succeeded his mentor Johannes Reinke on his chair at the Institute of Plant Physiology at the Georgia Augusta Göttingen until 1923. In this study we focus on the biography of Berthold, his private and scientific life, interaction with J. Reinke and other topics related to the life of Berthold. In a second part we highlight his research on algae at the Gulf of Naples. We conclude with an evaluation of his scientific work in the light of the different phases in his life including a full bibliography of his scientific publications. Our study contributes to history of science at the Georgia Augusta.